Tarım ürün sigortaları gelişimi ve uygulamalarının önemi - Yaman, İskender (My University, 1995)
MARMARA UNIVERSITY BANKING AND INSURANCE INSTITUTION INSURANCE DEPARTMENT THE EVALUATION OF THE DEVELOPMENT AND APPLICATIONS OF THE AGRICULTURAL INSURANCE IN TURKEY In Turkey, agriculture has played an important role in the development of industry for many years. Agriculture assists a nation's economy by producing raw materials to industry and by meeting the needs of population as food. However, agriculture has not been developed as the industry developed with the help of scientific and technological support. The ratio of population in countryside to overall population was 75.8 % in 1927, 75.6 % in 1940, 75 % in 1950. It started to decrease from the year of 1960 and it became 68.1 % in 1960, 61.5 % in 1970, 56 % in 1980 and 41 % in 1990. The number of people who live in countryside was 10.342.391 in 1927. It increased to 25.091.950 in 1980. Now 23.146.684 people live in countryside in Turkey. This number is 2.5 times is more than the number of people who live in countryside in Europe. However, the rate of agriculture in G.N.P (14.3 %) and in export (15.5 %) force us to deal with the existing problems that prevent the development of agriculture. Since agriculture has different properties with respect to other sectors, the problems encountered in agriculture are different than problems in other sectors. Our country has all favorite conditions for agriculture. In order to get maximum outcome from agriculture and assist for the development of economy, it is important to pay great attention on the organization of insurance. Although industrilization was accepted as the first aim for the development of Turkey after the foundation of Turkish Republic, agriculture conserved its importance. The importance of agriculture in economy can be listed as follows: 1- The rate of agricultural out come in GNP. 2- The rate of population in contryside to overall population. 3- The rate of agricultural products in overall export products. Agricultural activities are under the effect of natural, social and individual risks. The most important point that differs agriculture from other activities is the dependence of it on nature. Agriculture is under the effect of many disasters like wind, flood, drought, frost and hail. It is also affected by different plant diseases and harmful insects. Moreover, farmers are about to lose their investment for the future and their income because of the death of animals due to diseases and accidents, and the loss of worth. As a result of these types of loss, the farmers become poor and don't pay rental, tax, credits and dept. As a result, the depts of farmers start to increase. Under these conditions, it becomes too difficult for farmers to continue agricultural activities. For this reason, it is important to apply insurance activities in agriculture. Unfortunately, insurance has not been applied in agriculture in our country for many years. On the other hand, in other countries, governments support Agricultural Products Insurance. Agricultural Products Insurance is compulsory in some countries and optional in other countries. In any case governments support it by founding premium or loss. In our country, the government does not support it in any way. It is important to look at the development of insurance in other countries to reflect experiences obtained to develop insurance in our country. It is necessary to analyze the applications in developed countries in order to adapt them to the insurance system in our country. Most of the time, some serious problems emerge in the adaptation of the system of a country to another. First of all, it is important to explain farmers why they need insurance. It is the main idea in developed countries. The insurance system is organized upon this main idea. The scientific farming methods and production risks are taught to farmers, so that farmers having enough knowledge about insurance apply to insurance companies. By the development of the insurance against hail, agricultural products insurance starts to spread all over the country. It is not possible to give a guarantee against other risk without the development of insurance against hail. In developed countries, it is observed that insurance against frost, drought and flood has developed after the development of insurance against hail. It means that the following two rules must be applied before talking about multirisks and insurance. 1- To accept the insurance as a need. 2- To spread out insurance against hail. In order to spread out insurance against hail, it is important to educate farmers to be aware of new farming methods. Also it is important to place a course called Agricultural Insurance into the curriculum of the Faculty of Insurance. Recently many agriculturists have started to work in the field of agriculture. It would be better if they are educated for insurance. It is important to organize farmers by the foundation of Farmers Association. As a result, regional Farmers' Associations will try to spread out insurance. It is also important to support the foundation of JP' insurance agencies by farmers. It is also important to form Veterinary Surgeon Society for the development of Husbandary Insurance. In Japon, the government founds 70 % of the premium of the insurance against hail and also buys the products with a price of 3 times more than the price of the same product in stock markets. Although the rate of population in countryside to overall population is 1 % in developed countries, the conservation in $ 80 per 100 m.In our country,'the rate of population in countryside to overall population is approximately 50 % but the conservation is $ 4 per 1000 m2. The development of insurance depends on the policy of government. In our country, farmers don't want to found their loss with the help of insurance because the government founds their loss. For this reasons the laws that help farmers to found their loss from government are the most important obstacle in the development of insurance. Instead of these laws, the law of Agricultural Products Insurance must be applied. In order to form an effective agricultural insurance, first off all, these legal improvements must be done. After that the government must be forced to cooparate with insurance companies. The cooperation of the governmet with insurance companies can be one of the following ways: 1-To found premium 2-To found the expenses for administration and organization of insurance activities. 3 -To help insurance companies for reinsurance. 4-To support educational activities 5 -To establish an effective control mechanism 6-To conduct studies on the kinds of agricultural products that can be insured and the determination of loss rates for different regions. The coordination of some topics in Turkish Trade law will help for the adaptation of insurance sector to the laws applied in European countries. It also helps for the conservation of benefits of people who are insured, the increase in income of insurance companies the encouragement of people to pay their premium and depts and the development of insurance companies by means of financial activities. As a result it will help for the development of social and economical activities in our country. Nowadays, it is possible to observe the development of some concepts like Agricultural Insurance Agency, The Expert of Agicultural Insurance, The Found of Agricultural Insurance. Agriculturists must use the advantage of the recent developments in insurance to establish Hail Insurance Companies and Animal Insurance Companies so that they will share the pride of it. Moreover, they can form insurance for agricultural buildings, equipments, and transportation of agricultural products. Also they can form life insurance for farmers. As a result the life style of farmers will be improved to make them the sir of the nation as Atatürk said. For this reason, insurers have a great responsibility to develop insurance and then economy.
Keywords: Sigortacılık; Tarım_Sigortacılık